2021
DOI: 10.48550/arxiv.2103.09409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entanglement resource theory of quantum channel

Abstract: Quantum channels can represent dynamic resources, which are indispensable elements in many physical scenarios. To describe certain facets of nonclassicality of the channels, it is necessary to quantify their properties. In the framework of resource theory of quantum channel, we show two general ways of constructing entanglement measure of channels. We also present several entanglement measures of channels based on the Choi relative entropy of channels, concurrence and k-ME concurrence and give some specific ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Conventional entanglement theory focuses on the nonlocal correlation of quantum states, and quantum channels are used as their manipulation tool. Recent works have shown that quantum channel itself could be regarded as the resource object [17][18][19][20][21][22] and the entanglement of channels has be studied under the framework of quantum resource theories [23][24][25][26][27][28]. Analog to quantum states, quantum channels are also categorized into entangled and separable ones, with the amount of entanglement quantified via channel entanglement measures [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional entanglement theory focuses on the nonlocal correlation of quantum states, and quantum channels are used as their manipulation tool. Recent works have shown that quantum channel itself could be regarded as the resource object [17][18][19][20][21][22] and the entanglement of channels has be studied under the framework of quantum resource theories [23][24][25][26][27][28]. Analog to quantum states, quantum channels are also categorized into entangled and separable ones, with the amount of entanglement quantified via channel entanglement measures [23][24][25].…”
Section: Introductionmentioning
confidence: 99%